Attitude of First-Trimester Pregnant Women toward Warm Ginger Consumption for Reducing Nausea and Vomiting - Friska Oktaviana; Poppy Farasari (CV. Global Health Science Group, 2025)
Morning sickness is a common complaint experienced by pregnant women in the first trimester and is associated with hormonal changes, particularly increased levels of beta-human chorionic gonadotropin (β-hCG). One non-drug method often used to reduce nausea and vomiting is drinking warm ginger tea.This study aimed to determine the attitudes of pregnant women in their first trimester toward consuming warm ginger tea as a way to relieve nausea and vomiting. This study used a quantitative descriptive approach and selected participants through quota sampling. The group included 20 pregnant women in their first trimester who had morning sickness. Information was gathered using a Likert-scale questionnaire and was analyzed in a descriptive way. The tool used for collecting data was a questionnaire. The process of handling the data involved editing, coding, scoring, entering data, cleaning it, and organizing it into tables. Data were analyzed using frequency tables.A total of 85% of respondents expressed a positive attitude toward consuming warm ginger drinks, while 15% expressed a negative attitude.Most pregnant women in their first trimester have a positive attitude toward consuming warm ginger drinks as a non-pharmacological way to reduce nausea and vomiting.A healthy reproductive age and higher education level play a role in increasing pregnant women's ability to accept health information and their confidence in practicing consuming warm ginger to manage morning sickness.